Functional and behavioral effects of de novo mutations in calcium-related genes in patients with bipolar disorder. Issue 19 (7th June 2021) - Nakamura, Takumi; Nakajima, Kazuo; Kobayashi, Yuki; Itohara, Shigeyoshi; Kasahara, Takaoki; Tsuboi, Takashi; Kato, Tadafumi
Abstract: Bipolar disorder is a common mental illness occurring in approximately 1% of individuals and requires lifelong treatment. Although genetic factors are known to contribute to this disorder, the genetic architecture has not yet been completely clarified. Our initial trio-based exome sequencing study of bipolar disorder showed enrichment of de novo, loss-of-function (LOF) or protein-altering mutations in a combined group with bipolar I and schizoaffective disorders, and the identified de novo mutations were enriched in calcium-related genes. These findings suggested a role for de novo mutations in bipolar disorder. The validity of these statistical associations will be strengthened if the functional impact of the mutations on cellular function and behavior are identified. In this study, we focused on two de novo LOF mutations in calcium-related genes, EHD1 and MACF1, found in patients with bipolar disorder. We first showed that the EHD1 mutation resulted in a truncated protein with diminished effect on neurite outgrowth and inhibited endocytosis. Next, we used CRISPR/Cas9 to establish two knock-in mouse lines to model the in vivo effects of these mutations. We performed behavioral screening using IntelliCage and long-term wheel running analysis. Ehd1 mutant mice showed higher activity in the light phase. Macf1 mutant mice showed diminished attention and persistence to rewards. These behavioral alterations were similar to the phenotypes in previously proposed animal models of bipolar disorder. These findings endorse the possible role of de novo mutations as a component of the genetic architecture of bipolar disorder, which was suggested by the statistical evidence.